LA MOTIVACIÓN DURANTE EL PROCESO DE ENSEÑANZA APRENDIZAJE DE LA MATEMÁTICA Y SUS TECNOLOGÍAS EN LA EDUCACIÓN MEDIA EN LA CIUDAD DE ENCARNACIÓN (Journal on studies and research of academic knowledge, 2009)
This work was developed from an investigation project that it has objectives like to analyze, to describe, to uphold, strictly scientific, underlying involvement to the teacher work, exactly about the motivation that the mathematic teacher generates during the process of teaching – learning. The problem that turns around the teaching of Mathematics in education centers from Paraguay, considering the process of the educational reformation, in different levels, it is extremely complex with the purpose to look for the constant improvement through educational management,a research named “how to motivate during the teaching and learning process of Mathematics in middle  education in Encarnación”. To look for answers to the problem they have established as general objectives to find the way in which teachers of middle level in the area mathematics and their technologies of official schools in Encarnación motivate their students during the teaching and learning process to design a support theoretical model to the teaching direct to the improvement in classroom management, based in development considering the importance of motivation to achieve a significant learning. About epistolary orientation, the process of research trying to know the reality, it founds two phases, the first was limited in the quantitative paradigm, framed in descriptive research, because it fundamentally consists on characterizing how the variables in study are presented, and the second phase is based on qualitative paradigm, based on phenomenology to be able to consider what the students feel and live every day in classrooms. The reform of education was necessary and is also necessary to adjust aspects related to the Reform of Education, educational practices may be improved, but besides the will of the teacher is necessary to implement educational policies to tend toward daily improvement. About results they mention necessary information to justify the initial hypothesis, the reflection done by the researcher helped to elaborate a project that will be presented to the educational authorities about teaching perfection and a teaching material where you find suggestions, experiences and interesting pieces of information for motivating students and achieve significant learnings.
Keywords: Motivate; Teaching; Learning; Educational Reformation; Development; Mathematics; Middle Education; Strategic Educative Management